Superior vena cava syndrome in hemodialysis patient - Azeb Molhem; Alaa Sabry; Hassan Bawadekji; Khalid Al Saran (Saudi Journal of Kidney Diseases and Transplantation, 2011)
Obstruction of blood flow in the superior vena cava (SVC) results in symptoms and signs of SVC syndrome. SVC obstruction can be caused either by invasion or external compression of the SVC by contagious pathologic processes involving the right lung, lymph nodes, and other mediastinal structures, or by thrombosis of blood within the SVC. Occasionally, both mechanisms co-exist. We hereby report a case of a 28-year-old male, Saudi patient who was diagnosed with end-stage renal disease and was maintained on regular hemodiaysis via right jugular vein dual lumen catheter for ten months. Three years later, the patient presented with signs and symptoms suggestive of SVC obstruction that was successfully managed with SVC stenting.